Using Contribution of Menu Engineering in Upscale Restaurants to Enhance Sales Volume - Juliana, Juliana; Pramezwary, Amelda; Nukak, Novia A; Situmorang, Jimmy Muller Hasoloan (International Journal of Social and Management Studies, 2021)
Few menu analysis techniques have been embraced so readily and institutionalized as quickly as menu engineering. Hotel Istana Nelayan is a 3-star hotel located in Tangerang City, Banten. Hotel Istana Nelayan has a restaurant with various menu variants on the ala carte menu of Krakatau Resto and Coffee Shop. This research aims to review the application of menu engineering analysis in increasing sales volume at the Istana Nelayan Hotel. The research method uses a qualitative approach using descriptive analysis with the menu engineering analysis method. This analysis uses the popularity index and contribution margin method. The study showed that the ala carte menu has four classifications: scilicet 8 Star, 5 Plowhorse, 4 Puzzle, and 2 Dog. Therefore, more detailed performance data has been provided regarding menu items. From the restaurant manager's perspective, this means that the analysis results can be served both short and long-term business goals. Keywords — Istana Nelayan Hotel, Engieering Menu, Sales Volume